COLONIC ATRESIA AND STENOSIS: OUR EXPERIENCE - Bilal Mirza; Shahid Iqbal; Lubna Ijaz (EL-Med-Pub, 2012)
Background: Colonic atresia and stenosis are rare entities. On average 1 case per year of colonic atresia is being seen in most of pediatric surgical centers and to date less than 10 cases of colonic stenosis have been reported.Material and Methods: The medical record of patients of colonic atresia and stenosis managed during March 2006 to March 2010 was reviewed. Results: A total of 15 patients of colonic atresia (11) and stenosis (4) were the study population. Four were ascending colon atresia, 2 at hepatic flexure and transverse colon each, and 1 at sigmoid colon. Two patients had multiple colonic atresias. One patient of ascending colon atresia also had pyloric atresia. In colonic stenosis population (two congenital and two secondary to necrotizing enterocolitis), two were transverse colon stenosis and two were sigmoid colon stenosis. The preoperative diagnosis was distal small bowel atresia in 11 patients. Colonic atresias were managed by colocolic anastomosis with covering ileostomy in 8 patients. The remaining 3 patients were managed by exteriorizing both ends of atresia. Colonic stenosis cases were managed by primary colocolic anastomosis in 1 patient and colocolic anastomosis under covering ileostomy in 3 patients. Three patients of colonic atresia succumbed postoperatively. Conclusion: Colonic atresia and stenosis are rare entities. Associated alimentary tract malformations may result poor prognosis. Colonic atresia can safely be managed by colocolic anastomosis with covering ileostomy.